Kinetic parameters for thermal decomposition of hydrazine - Santos, L. B.; Ribeiro, Clovis Augusto [UNESP]; Capela, Jorge Manual Vieira [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Pimentel, M. A S; De Julio, M. (Springer Nature, 2013)
The propulsion of most of the operating satellites comprises monopropellant (hydrazine - N2H4) or bipropellant (monometilydrazine - MMH and nitrogen tetroxide) chemical systems. When some sample of the propellant tested fails, the entire sample lot shall be rejected, and this action has turned into a health problem due to the high toxicity of N2H 4. Thus, it is interesting to know hydrazine thermal behavior in several storage conditions. The kinetic parameters for thermal decomposition of hydrazine in oxygen and nitrogen atmospheres were determined by Capela-Ribeiro nonlinear isoconversional method. From TG data at heating rates of 5, 10, and 20 C min-1, kinetic parameters could be determined in nitrogen (E = 47.3 ± 3.1 kJ mol-1, lnA = 14.2 ± 0.9 and T b = 69 C) and oxygen (E = 64.9 ± 8.6 kJ mol-1, lnA = 20.7 ± 3.1 and T b = 75 C) atmospheres. It was not possible to identify a specific kinetic model for hydrazine thermal decomposition due to high heterogeneity in reaction; however, experimental f(α)g(α) master-plot curves were closed to F 1/3 model. © 2013 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Hydrazine; Non isothermal kinetic; Propellant; Thermal decomposition; Decomposition of hydrazine; High heterogeneity; Iso-conversional method; Nitrogen tetroxide; Non-isothermal kinetic; Oxygen and nitrogens; Storage condition; Thermal behaviors; Decomposition; Digital storage; Kinetic parameters; Nitrogen; Nitrogen oxides; Oxygen; Propellants; Pyrolysis